2020
DOI: 10.1186/s13063-020-04663-x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of ear acupressure (auriculotherapy) on sexual function of lactating women: protocol of a randomized sham controlled trial

Abstract: Background: Lactation has a negative effect on female sexual function. Hormonal changes during lactation cause changes which might lead to dyspareunia, lack of libido, and anorgasmia. There are various pharmacological and non-pharmacological approaches to treat sexual dysfunction. While pharmacological treatment has multiple unwanted side effects, non-pharmacological therapies such as complementary medicine are a potential safer alternative. The aim of this study is to evaluate the effect of ear acupressure on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Moxibustion [ 9 ] and ear acupressing bean therapy [ 10 ] are the treasures of Chinese medicine, and research on moxibustion and ear acupressing bean therapy for vertigo has been in constant development in recent years. Studies [ 11 , 12 ] have shown that stimulating the corresponding response points and acupuncture points in the auricle can help regulate the qi and blood of the internal organs, balance yin and yang, unblock the meridians, and tonify the kidneys and strengthen the spleen, thus achieving a calming and tranquilizing effect and stopping dizziness. In addition, the warmth of the moxibustion fire can be used to stimulate the body, eliminating stagnation, raising the Yang and Qi, and warming the meridians and invigorating the blood, thus promoting the glory of Qi and blood and nourishing the brain, which can effectively suppress vertigo.…”
Section: Introductionmentioning
confidence: 99%
“…Moxibustion [ 9 ] and ear acupressing bean therapy [ 10 ] are the treasures of Chinese medicine, and research on moxibustion and ear acupressing bean therapy for vertigo has been in constant development in recent years. Studies [ 11 , 12 ] have shown that stimulating the corresponding response points and acupuncture points in the auricle can help regulate the qi and blood of the internal organs, balance yin and yang, unblock the meridians, and tonify the kidneys and strengthen the spleen, thus achieving a calming and tranquilizing effect and stopping dizziness. In addition, the warmth of the moxibustion fire can be used to stimulate the body, eliminating stagnation, raising the Yang and Qi, and warming the meridians and invigorating the blood, thus promoting the glory of Qi and blood and nourishing the brain, which can effectively suppress vertigo.…”
Section: Introductionmentioning
confidence: 99%
“…The shoulder is represented in the areas SF1 and SF2 (Figure 2). 21 Primary objective was to evaluate efficiency of NCT as viable diagnostic option to identify the most appropriate AA acupoints to be selected for treatment of shoulder pain associated with SST. Outcome measurements used were pain assessment with Numeric Pain Rating Scale (NPRS) and affected shoulder Range of Movements (ROM).…”
mentioning
confidence: 99%